Handbook of blockchain, digital finance, and inclusion. - Lee, David (David Kuo Chuen); Deng, Robert H. (Academic Press, 2018)
Handbook of Blockchain, Digital Finance, and Inclusion, Volume 1: Cryptocurrency, FinTech, InsurTech, and Regulation explores recent advances in digital banking and cryptocurrency, emphasizing mobile technology and evolving uses of cryptocurrencies as financial assets. Contributors go beyond summaries of standard models to describe new banking business models that will be sustainable and will likely dictate the future of finance. The volume not only emphasizes the financial opportunities made possible by digital banking, such as financial inclusion and impact investing, but it also looks at engineering theories and developments that encourage innovation. Its ability to illuminate present potential and future possibilities make it a unique contribution to the literature. Explores recent advances in digital banking and cryptocurrency, emphasizing mobile technology and evolving uses of cryptocurrencies as financial assets Explains the practical consequences of both technologies and economics to readers who want to learn about subjects related to their specialties Encompasses alternative finance, financial inclusion, impact investing, decentralized consensus ledger and applied cryptography Provides the only advanced methodical summary of these subjects available today.